Composition Diversity and Expression Specificity of the TPS Gene Family among 24 Ficus Species - Peng Sun; Xiaoyong Chen; Bhanumas Chantarasuwan; Xueying Zhu; Xiaoxia Deng; Ying Bao; Hui Yu (Diversity, 2022)
Volatile organic compounds (VOCs) released by the receptive syconia of Ficus species play a vital role in attracting highly species-specific pollinating fig wasps. The components of VOCs vary considerably among Ficus species, but are generally dominated by a few common terpenoid compounds or specific proportions of several compounds. Terpene synthase (TPS) is the main source of specific and diverse terpenoids, but the evolution of the TPS gene family in Ficus and the potential functions of the TPS genes in species-specific pollination remain largely unelucidated. In this study, using transcriptomes of ostiole bracts of receptive male figs from 24 Ficus species collected from South China and Southeast Asia, we comprehensively scanned and investigated the composition and evolutionary characteristics of all TPS genes in all 24 species. We identified 248 TPS genes, including 33 orthologous genes and six singletons. Sequence and phylogenetic analysis showed that a majority of the 248 TPSs contained the DDXXD and DTE motifs, rather than the DXDD motif, and involved all subfamilies (TPS-a,b,c,e/f and g) known in other angiosperm genomes, suggesting a very diverse and complex composition of class I TPSs during the receptive phase. In addition, compared to TPS-a, which is generally the largest subfamily in some plants, the TPS-b subfamily contained the highest number of genes in Ficus species. Expression profile comparison showed that the distribution and expression levels of different TPSs among different Ficus species differed considerably, but a few TPS genes were common across most species. Positive selection analysis showed that the Ficus TPS genes were mainly under purifying selection, with only four genes having positive selection signals and two genes having positive selection sites, and two genes having relatively fast-evolving rates. The present study demonstrates the basic evolutionary characteristics of TPS genes in Ficus and reveals the roles of TPSs in shaping the diversity and specificity of the fig–fig wasp symbiotic relationship.